Women on the Role of Public Higher Education
XIII, 251 p.
Keywords: This edited collection presents a compilation of personal essays on the role of public higher education in the lives of fourteen social scientists who are graduates of the Graduate Center, the doctoral granting institution at the City University of New York, the nation's largest public urban university.